Exploring the Interpersonal Meaning through the USE of Mood System in Dialogue Texts of English for Nusantara Textbook - Nurauliya, Salsafadilah; Setia Samsi, Yogi; Wachyudi, Kelik (Edukasiana: Jurnal Inovasi Pendidikan, 2026)
This study addressed the problem of how mood system represents interpersonal meaning and construct social relationships in dialogue texts of English for Nusantara textbook. This study employed a qualitative research method using content analysis under the framework of Systemic Functional Linguistics (SFL). The method focused on analyzing dialogue texts from the English for Nusantara textbook to identify and interpret mood, modality, and speech functions that construct interpersonal meaning in English language learning contexts. The findings revealed that declarative clauses dominated the dialogue texts, followed by interrogative and imperative forms. Low and medium modality values were frequently used to express politeness and encouragement. These patterns indicate that the English for Nusantara textbook emphasizes information exchange and cooperative interaction which reflecting harmonious and student-centered communication. The study concludes interpersonal meaning in the dialogue texts of English for Nusantara Textbook is constructed through the combination between mood and modality system. The mood structure construct interpersonal meaning and reflects the purpose of language as a medium in building relationship and negotiating roles. While, modality acts as a bridge for speakers to convey attitude and stance. Another metafunction, such as ideational or textual meaning, is highly recommended for future studies.